PENGARUH SUHU PROSES TERHADA P SINTESIS ALKYD RESIN DARI DAUN KEMANGI (OCIMUM BASILICUM) SEBAGAI BAKAL BINDER PEMBUATAN CAT - Paparingan, Theodorus Cahyo; Pasaribu, Dony Syamsuddin Halomoan; Qoyyim, Fatah Ibnul; Purwanti, Ani (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
Alkyd resin are an example of a polymer product formed by the condensation polymerization process. Alkyd has great value when modified with natural oils or synthesis (triglycerides). This study aims to determine the effect of temperature on the mechanical properties of alkyd resin. The research process consists of 4 stages: the extraction process, the distillation process, the alcoholysis reaction and the esterification reaction. The study began by extracting essential oils from dried basil leaves. Extraction is done using n-hexane solvent which will be removed in the distillation process. The alcoholysis begins by reacting basil essential oil with glycerin in a volume ratio of 1:5 at 180oC. Then the esterification step is carried out by mixing phthalic anhydride into a batch reactor with a molar ratio of glycerol:phthalic anhydride 3:2. Then analyze aspects of viscosity, acid numbers, iodic numbers, and colors. The results obtained in the analysis showed a process temperature of 180oC more effectively used for further research processes because of the compatibility of the results with the alkyd resin reference value. The results obtained are 189516 cP viscosity, acid number 6,83935 mg/g, iodic number 1,8935 mg/g, and a dark yellow color.